1986
DOI: 10.1104/pp.82.2.494
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Stimulation of Uptake Hydrogenase Activity In Symbiotic Rhizobium

Abstract: Initial observations showed a 100% increase in Hruptake (Hup) activity of Rhizobium legumixosarum strain 3855 in pea root nodules (Pisum sativum L. cv Alaska) on plants growing in a baked clay substrate relative to those growing in vermiculite, and an investigation of nutrient factors responsible for the phenomenon was initiated. Signifiantly greater Hup activity was first measured in the clay-rown plants 24 days after germination, and higher activity was maintained relative to the vermiculite treatment unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…3. Kapulnik and Phillips [44] showed that the sodium ion stimulates hydrogenase activity in pea root nodules containing Rhizobium leguminosarum bacteria.…”
Section: Effect Of Different Concentrations Of Na 2 Co 3 and Nahco 3 mentioning
confidence: 99%
“…3. Kapulnik and Phillips [44] showed that the sodium ion stimulates hydrogenase activity in pea root nodules containing Rhizobium leguminosarum bacteria.…”
Section: Effect Of Different Concentrations Of Na 2 Co 3 and Nahco 3 mentioning
confidence: 99%
“…In symbiotic rhizobia, the Hup system is affected by the host plant. Thus, environmental factors perceived by the plant, such as irradiance (6) and salinity (18), alter Hup activity. Unexplained effects of host plant genotype on Hup activity also occur in different plant species nodulated by the same rhizobia (10,12,19,21,23).…”
mentioning
confidence: 99%